MENINGKATKAN KETERAMPILAN MEMASANG BAJU MELALUI ANALISIS TUGAS BAGI ANAK TUNAGRAHITA SEDANG DI SLB NEGERI 1 PADANG - Fitri, Nur Ilahia (RC-INSTITUT, 2019)
This study discusses mentally retarded children who are in class I in SLB Negeri 1 Padang who have difficulty in developing themselves especially in putting on their clothes properly. At the time the researcher made observations on how to put on clothes the child could not unbutton the clothes and put them in the right way and the child did not know the parts of the clothes. This study aims to determine the effectiveness of task analysis in improving the skill of putting clothes on moderate retarded children. The research method used is single subject research with A-B-A design and data analysis techniques using graph visual analysis. To measure the variable using a percentage of the number of instrument items. The results of his research showed an increase in children's skills in posing positively, where at baseline (A1) and intervention (B) conditions overlap 0% and at baseline (A2) conditions they overlap 50%. Based on these results it is concluded that an effective task analysis is used to improve the skills of putting clothes on for mentally retarded children.